Delayed retropharyngeal hematoma following a minor facial blunt trauma. (April 2021) - Kitai, Yuya; Sato, Ryota
Abstract: We described the case of 75 years old male patient with an airway obstruction due to retropharyngeal hematoma that developed after a minor blunt trauma to the face. The patient was not taking any anticoagulants or antiplatelet agents and did not have any coagulopathy. This case report indicates that emergency physicians must be aware of the risk of delayed airway obstruction in elderly patients regardless of whether the patient is using anticoagulants or antiplatelet agents.